Scalp Reconstruction after Malignant Tumor Resection: An Analysis and Algorithm - Ehrl, Denis; Brueggemann, Alexandra; Broer, P. Niclas; Koban, Konstantin; Giunta, Riccardo; Thon, Niklas (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background An oncologic tumor resection of the scalp can result in complex wounds that result in challenging scalp reconstructions. This study aimed to evaluate the outcomes of microvascular-based scalp reconstructions (MSR) in oncologic patients and to propose an algorithmic treatment approach.Methods Within a 5-year period, 38 patients having undergone 41 MSR (15 anterolateral thigh (ALT), 15 gracilis muscle (GM), and 11 latissimus dorsi muscle (LDM) flaps) after extensive scalp tumor resections fulfilled inclusion criteria for this study.Results Malignant skin disease included superficial and/or deep infiltration of the calvarium in 26 and combined intracranial infiltration in 12 patients. In case of bone replacement (24 patients), MSR was done concomitant, otherwise MSR was performed after pathological confirmation of tumor-free margins. LDM flaps were used in cases with defect sizes of 400 to 1250cm2, whereas ALT- and GM flaps were chosen for defects ranging from 40 to 350cm2. The average length of the pedicle was comparable in ALT- and LDM flaps and longer than in GM flaps. Total flap loss with need for revision surgery and minor donor site morbidity occurred in four and three patients, respectively.Conclusion Microsurgical reconstruction of moderate-to-extensive scalp defects remains a reliable method with overall low risks and satisfactory aesthetic results, while, according to our experience, muscle flaps show the best functional and aesthetic results. However, in cases of central scalp defects and in situations when a long vascular pedicle of the flap is important, the ALT flap seems to be the best solution.
Keywords: scalp; reconstruction; gracilis muscle flap; anterolateral thigh flap; latissimus dorsi muscle flap; tumor resection